The oldest and the newest - Marsico, Katie, 1980- (New York : Scholastic, 2016)
"Learn all about the oldest and newest places on Earth and find out how the world has changed over time."
Keywords: Antiquities -- Juvenile literature; Trees -- Age determination -- Juvenile literature; Volcanic eruptions -- Juvenile literature; Barnenez Cairn (France) -- Juvenile literature